Impact of supply and exhaust ventilation system on gas concentrations in a compartment during thermal decomposition and combustion of materials; Fire Safety Journal; Vol. 147 - Volkov R. S. Roman Sergeevich; Kuznetsov G. V. Geny Vladimirovich; Sviridenko A. S. Aleksandr Sergeevich; Strizhak P. A. Pavel Alexandrovich (2024, 2024)
Title screen